Performance analysis of truncated ARQ and HARQ I protocols for cooperative networks using smart amplify and forward relaying. (5th June 2019) - Halima, Nadhir Ben; Boujemâa, Hatem
In this paper, we evaluate the theoretical performance of truncated automatic repeat request (ARQ) and Hybrid ARQ I protocols with and without packet combining in cooperative networks using smart amplify and forward relaying. In cooperative networks, the retransmission can be done by the source or by a selected relay. The selected relay is the one which offers the best instantaneous signal to noise ratio (SNR) of the relaying link. We provide a theoretical framework when there is a combination of source and relays transmission for a destination using a maximum ratio combining of the received packets from the source and the relays. Smart relays are studied in this paper. These relays selected the best packet from the source. We will show that the performance is better for smart relays that continuously supervise the transmissions from the source compared to conventional relays overhearing only the first source transmission. We also suggest smart relays listening to each other.